Game number of double generalized petersen graphs - Muhammad Shahzad Akhtar,; Syed Ahtsham Ul Haq Bokhary, (Utilitas Mathematica, 2022)
The game chromatic number χg of double generalized petersen graph DP (n, m) is investigated. The definite values for the game chromatic number of DP (n, 1), DP (n, 2), DP (n, 3) and DP (n, m) are determined. These results extend the previous work of Shaheen, Ramy, Ziad Kanaya and Khaled Alshehada, who ex- plored the game chromatic number of generalized petersen graphs and jahangir graphs.